Enseñanza eficaz de la resolución de problemas en matemáticas - Salas Soto, Silvia Elena (2008)
This article comes from the current concern about the student's low performance in mathematics, as a factor that has caused many of them to drop the school and repeat the same grade. Problem solving has been considered one of the most difficult areas of mathematics for students. Even though boys and girls are able to solve mechanically basic arithmetic operations (addition, subtraction, multiplication, and division), they do not know how to apply them for solving problems. This is because students have been taught to act in a mechanical and repetitive way. Therefore, it is important to make people conscious about this situation of the Costa Rican educational system. In addition, specific actions must be taken in order to improve the teaching-learning processes of the problem solving.